(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to determine the relationship between quality of life and urinary incontinence in children.Material and Methods: This study was carried out with the cross-sectional research model, one of the observational analytical research models. The study was conducted between November 2018 and December 2019 at the urology outpatient clinic of Necmettin Erbakan University Hospital. The sample of the study consisted of fifty one pediatric patients between the ages of 5 and 18 years who were selected by using the simple random sampling method, were able to communicate and volunteered to participate in the study. The data were obtained through the face-to-face interview method using a Patient Demographic Information Form, the Dysfunctional Voiding and Incontinence Symptoms Score Questionnaire (DVISS), the Dysfunctional Voiding Symptom Score (DVSS) and the Pediatric Urinary Incontinence Quality of Life Score (PIN-Q). The data are expressed as percentage, mean and standard deviation. Results: Among the patients participating in the study, the mean Dysfunctional Voiding and Incontinence Symptoms Score was found as 17.07 ± 5.12. In this study, a significantly positive correlation was found between DVISS and DVSS and PIN-Q. There was a significant relationship between PIN-Q dimensions and DVISS and DVSS.Conclusion: Pin-Q and DVSS are complementary and offer clinical effects. This study showed that there is a correlation between urinary incontinence and quality of life.